2012
DOI: 10.1016/j.rbmo.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of Oct-4 and acetylated H4K5 in rabbit embryos

Abstract: Rabbit is a unique species to study human embryology; however, there are limited reports on the key transcription factors and epigenetic events of rabbit embryos. This study examined the Oct-4 and acetylated H4K5 (H4K5ac) patterns in rabbit embryos using immunochemistry staining. The average intensity of the Oct-4 signal in the nuclei of the whole embryo spiked upon fertilization, then decreased until the 8-cell stage and increased afterwards until the compact morula (CM) stage. It decreased thereafter from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
4
24
1
Order By: Relevance
“…This could in turn reflect in the expression of other genes. The peak expression at ZGA phase in this study shows a positive correlation to the lowest acetylation levels in rabbit embryo reported earlier [40]. In cattle, HDAC1 expression in the in vitro embryos was low until 8-cell stage, but increased eight to ten times at the blastocyst stage [52].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This could in turn reflect in the expression of other genes. The peak expression at ZGA phase in this study shows a positive correlation to the lowest acetylation levels in rabbit embryo reported earlier [40]. In cattle, HDAC1 expression in the in vitro embryos was low until 8-cell stage, but increased eight to ten times at the blastocyst stage [52].…”
Section: Discussionsupporting
confidence: 74%
“…In the bovine blastocysts, a similar OCT4 localization was reported [59,73]. A nuclear localisation in the early stages of rabbit development and a decline in protein levels recovering after ZGA were reported earlier [40]. The difference in these observations needs to be addressed further.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In support of this notion, it has been shown that, compared to mouse embryos, rabbit embryos have a more similar pattern of preimplantational development and lineage formation to that of human embryos. For example, in human and rabbit embryos, Oct4 expression was present in both the inner cell mass (ICM) and the trophectoderm (TE) cells (Berg et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Hansis et al, 2000;Kirchhof et al, 2000), whereas in mice, Oct4 is expressed restrictively in the ICM, but not in the TE (Dietrich and Hiiragi, 2007;Ovitt and Scholer, 1998;Palmieri et al, 1994;Pesce et al, 1998;Yeom et al, 1996).…”
Section: Discussionmentioning
confidence: 99%